Challenges to brand Australia: international students and the problem with speaking - Yates, Lynda; Wahid, Ridwan (Routledge, 2013)
Although communication skills in English are important for both their career prospects and the success of their overall study experience, many international students find their spoken English a barrier to employment after graduation. In this paper, we draw on longitudinal interview data from international postgraduates to investigate the individual and social factors that impacted on the development of their speaking skills as they studied in Australia. Our findings suggest that, despite high levels of motivation to improve, they received little instruction in such skills on their English for Academic Purposes programs and had little access to them in the community. We argue that for compelling moral as well as economic reasons universities urgently need to address these issues through both instruction and social integration initiatives if they are to safeguard their lucrative but vulnerable overseas markets.